THE EFFECT OF FLAVONOID PROPOLIS KELULUT (Trigona spp) EXTRACT ON MACROPHAGE CELL NUMBER IN PERIODONTITIS (IN VIVO STUDY IN MALE WISTAR RATE (Rattus novergicus) GINGIVA) - Makfiyah Saidah; Beta Widya Oktiani; Irham Taufiqurrahman (FKG Unlam, 2020)
Background : Periodontitis is a condition where there is an increase in the number of inflammatory cells, namely macrophages in periodontal tissue. Macrophag cell is 12-15μm in oval shape cell with purplish blue cytoplasm and this cell’s function is to phagocytes bacteria and infiltrate gingival tissue. Propolis kelulut contains flavonoid that have an anti-inflammatory effect by suppressing the signal pathway p38 MAPK, JNK 1/2 and NF-kB that it can reduce the number of macrophage cells in inflammatory periodontal tissues. Objective: The purpose of this study was to determine the effect of 0.5 mg dose flavonoid propolis extract on the number of macrophage cells in gingiva wistar rats that have been made into a periodontitis condition. Method: This study used a pure experimental method with a post test only with control group design. There were 9 treatment groups, including flavonoid propolis extract on 1,3,5 days, ibuprofen gel on 1,3,5 days and negative control on 1,3 dan 5 days. Results: There was an effect of giving 0.5 mg flavonoids propolis kelulut extract to the number of macrophage cells in periodontitis. Conclusion: Flavonoid propolis kelulut extract has an effect in increasing the number of macrophage cells on day 3 and decreasing the number of macrophage cells on the 5th day.